The Molecular and Physiological Basis of Nutrient Use Efficiency in Crops 2011
DOI: 10.1002/9780470960707.ch16
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in Soils and Crop Nutrition

Abstract: Zinc (Zn) is an essential micronutrient and has particular physiological functions in all living systems, such as the maintenance of structural and functional integrity of biological membranes and facilitation of protein synthesis and gene expression. Among all metals, Zn is needed by the largest number of proteins. Zinc-binding proteins make up nearly 10 % of the proteomes in eukaryotic cells, and 36% of the eukaryotic Zn-proteins are involved in gene expression (Andreini et al., 2006, J. Proteome Res. 5: 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(60 citation statements)
references
References 336 publications
1
58
1
Order By: Relevance
“…It was reported that when genotypes grown on soils with low micronutrient availability due to chemical or biological fixation, or spatial or temporal unavailability, micronutrient-efficient genotypes have greater yield in comparison to inefficient genotypes even when fertilized with smaller amounts or less frequently [ 58 ]. The importance of genotype on differential micronutrient efficiency has been previously reported and discussed in detail [ 59 , 60 , 61 ]. The current research demonstrated that several CS lines had higher concentration of micronutrients compared to the parent TM-1 line, suggesting the potential association of the substituted chromosome or chromosome segment pair of the traits of interest.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that when genotypes grown on soils with low micronutrient availability due to chemical or biological fixation, or spatial or temporal unavailability, micronutrient-efficient genotypes have greater yield in comparison to inefficient genotypes even when fertilized with smaller amounts or less frequently [ 58 ]. The importance of genotype on differential micronutrient efficiency has been previously reported and discussed in detail [ 59 , 60 , 61 ]. The current research demonstrated that several CS lines had higher concentration of micronutrients compared to the parent TM-1 line, suggesting the potential association of the substituted chromosome or chromosome segment pair of the traits of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In leaves, Cu was reduced by 32% and 40% at 250 and 500 mg/kg, respectively, compared with control. It has been reported that high levels of Zn can reduce Cu uptake, by an antagonist interaction [27], due to both elements sharing the same transporters [53].…”
Section: Effects In Micronutrient Accumulationmentioning
confidence: 99%
“…Plants generally absorb Zn as a divalent cation (Zn ++ ). Zinc is required in protein biosynthesis and carbohydrate metabolism, and plays an important role in gene expression related to environmental stress [5,6]. Although Zn is required by plants for optimal metabolism, the efficiency of this micro-element depends on its absorption and translocation [7].…”
Section: Introductionmentioning
confidence: 99%